Ответ(ы) на вопрос:
Гость
[latex](x-8)(x^2-7x-8)=x^3-8x^2[/latex] [latex](x-8)(x^2-7x-8)=x^2(x-8)[/latex] [latex]x^2-7x-8-x^2=0[/latex] [latex]7x=-8[/latex] x[latex]x=-8/7[/latex]
Гость
[latex](x-8)(x^2-7x-8)=x^3-8x^2[/latex] [latex](x-8)(x^2-7x-8)=x^2 (x-8)[/latex] [latex](x-8)(x^2-7x-8)-x^2 (x-8)=0[/latex] [latex](x^2-7x-8-x^2 )(x-8)=0[/latex] [latex] x^2-7x-8-x^2=0;x-8=0[/latex] [latex] -7x-8=0;x=8[/latex] [latex] -7x=8[/latex] [latex] x=-8/7[/latex] [latex]-8/7;8.[/latex]
Не нашли ответ?
Похожие вопросы